An Approach to Domain Transfer in Procedural Content Generation of Two-Dimensional Videogame Levels - Snodgrass, Sam; Ontanon, Santiago (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2016)
Statistical models, such as Markov Chains, have been recently studied in the context of procedural content generation (PCG). These models can capture statistical regularities of a set of training data and use them to sample new content. However, these techniques assume the existence of sufficient training data with which to train the models. In this paper we study the setting in which we might not have enough training data from the target domain, but we have ample training data from another, similar domain. We propose an algorithm to discover a mapping between domains, so that out-of-domain training data can be used to train the statistical model. Specifically, we apply this to two-dimensional level generation, and experiment with three classic video games: Super Mario Bros., Kid Icarus and Kid Kool.